PROFILE INTEGRATED SCIENCE WORKSHEET BASED ON INQUIRY WITH THE THEMES “THE INFLUENCE OF ADDICTIVE SUBSTANCES TO THE HUMAN EXCRETION SYSTEM” IN CLASS IX JUNIOR HIGHT SCHOOL - JEFRI EKO PUJIANTO (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Abstract. This research was intended to produce integrated science students’ worksheet inquiry based which was theoretically appropriate. This type of research is the development based on Kemp’s model development. In this research, the data collection method used was the students’ worksheet validation of inquiry to determine the feasibility of the theory, questionnaire to determine students' responses toward the students’ worksheets had been developed, the observation of the students’ activity during teaching and learning by using worksheets, and a test that was used to measure the indicators. The results of this research were integrated science students’ worksheet inquiry based by the theme "The influence of addictive substances on the human excretory system" class IX of junior high school. These worksheets were theoretically feasible stated with the eligibility of the score 80,56%. Keywords: inquiry based, The Influence of addictive substances on the human excretion system, Worksheet Integrated Science Based.